Linhagem, gênero e idade dos frangos de corte e sua influência na umidade, proteína e relação umidade proteína na carne do peito coletados antes da etapa de pré-resfriamento - Zucatto, Daniela Aparecida de Almeida (2021)
Some chicken cuts have established limits for moisture, protein and moisture-protein ratio (RUP), defined by Normative Instruction No. 32 of 2010 from MAPA. According to this legislation, skinless breast meat samples must have a moisture content between 73.36 and 75.84%, a protein index between 21.05 and 24.37% and a protein moisture ratio (RUP) between 3 .03 and 3.55% for the final product. However, the meatpacking industries have been facing difficulties in meeting the official requirements regarding the physical and chemical parameters of the cuts, which is having a negative impact on the industrial sector due to the fines issued by the inspection agency, with spillovers on credibility with the consumer. If the objective of the legislation is to prevent frauds related to the addition of exogenous water to products, one must consider, on the other hand, the possibility that the genetic evolution of chickens over the years has affected the composition of the carcass as a whole. This work analyzed the influence of strain (Cobb and Ross), sex (male and female) and age (< or=41 days or >41 days) on the results for moisture, protein and RUP of skinless chicken breast meat, collected before the precooling step. For this experiment, 96 skinless chicken breast samples were used, collected in a refrigerated slaughterhouse under the Federal Inspection Service. Before the slaughter stage, the birds were selected to compose the study variables, following the normal slaughter flow until the final shower located in the evisceration sector, where they were removed from the line to cut the skinless breast. All samples were collected before the pre-cooling stage and after freezing were sent to a MAPA accredited laboratory to determine the physical-chemical parameters, following the methodologies: Protein (wet base) - ISO 1871:2009, Moisture and volatiles - ISO 1442:1997 and Moisture/protein ratio: MAPA Manual 1.15. Based on the analysis of the results, it was possible to observe that 50% of these samples had moisture above the maximum limit (75.84%), for the protein index 8.33% of the results were below the minimum limit (21.05%) and 19.79% of the results for RUP were above the maximum limit (3.55%). The data also showed that samples from males of the Ross lineage and older than 41 days showed the greatest deviations for moisture, protein and RUP, indicating that the studied parameters (sex, lineage and age range) may contribute to the non-compliance with IN nº32, since the cuts of skinless breasts from these carcasses presented deviations even before being sent to the pre-cooling system.